2021
DOI: 10.1101/2021.09.23.461469
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Constitutive depletion of brain serotonin differentially affects rats’ social and cognitive abilities

Abstract: Background: Central serotonin is an essential neuromodulator for mental disorders. It appears a promising transdiagnostic marker of distinct psychiatric disorders and a common modulator of some of their key behavioral symptoms. We aimed to identify the behavioral markers of serotonergic function in rats and compare them to human deficits. Methods: We applied a comprehensive profiling approach in adult male Tph2-/- rats constitutively lacking central serotonin. Under classical and ethological testing conditions… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 125 publications
(116 reference statements)
2
2
0
Order By: Relevance
“…As 5-HT regulates the aggression in both sexes, enhanced serotonergic activity could inhibit intermale aggression, while hindering 5-HT signaling will stimulate aggression. , 5-HT transporter knockout rats exhibit less aggression, more prosocial behaviors with a high sensitivity to social stimuli . In our case, Tph2 –/– rats had outburst aggressive behaviors almost immediately when housed together with another rat in a novel environment (data not shown), as reported Tph2 –/– rats have more dense social networks, a more unstable hierarchy, and normal social memory . Therefore, we propose that Tph2 –/– rats have a deficit in updating environmental information, leading to disrupted transmission of social information like hierarchy and social network.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…As 5-HT regulates the aggression in both sexes, enhanced serotonergic activity could inhibit intermale aggression, while hindering 5-HT signaling will stimulate aggression. , 5-HT transporter knockout rats exhibit less aggression, more prosocial behaviors with a high sensitivity to social stimuli . In our case, Tph2 –/– rats had outburst aggressive behaviors almost immediately when housed together with another rat in a novel environment (data not shown), as reported Tph2 –/– rats have more dense social networks, a more unstable hierarchy, and normal social memory . Therefore, we propose that Tph2 –/– rats have a deficit in updating environmental information, leading to disrupted transmission of social information like hierarchy and social network.…”
Section: Resultssupporting
confidence: 64%
“…9 In our case, Tph2 −/− rats had outburst aggressive behaviors almost immediately when housed together with another rat in a novel environment (data not shown), as reported Tph2 −/− rats have more dense social networks, a more unstable hierarchy, and normal social memory. 14 Therefore, we propose that Tph2 −/− rats have a deficit in updating environmental information, leading to disrupted transmission of social information like hierarchy and social network. At the same time, we noticed that Tph2 −/− rats spent more time on social contact with their assigned partner, but in an 'antisocial' manner with increased mounting behavior.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Serotonin transporter knockout rats exhibit less aggression, more prosocial behaviors with a high sensitivity to social stimuli (Homberg & Lesch, 2011). In our case, Tph2 -/- rats had outburst aggressive behaviors almost immediately when housed together with another rat in a novel environment (Supplementary Fig1), as reported Tph2 -/- rats have more dense social networks, a more unstable hierarchy and normal social memory (Alonso et al, 2021). Therefore, we propose that Tph2 -/- rats have a deficit in updating environmental information, leading to disrupted transmission of social information like hierarchy and social network etc.…”
Section: Discussionsupporting
confidence: 81%
“…These results may indicate serotonergic hyperactivity in the manic phase and hypoactivity in the depressive phase [ 239 ]. Studies in mice have also shown that serotonin deficiency causes aggressive and overly sexual behavior similar to that of patients in the manic phase [ 240 ].…”
Section: Resultsmentioning
confidence: 99%